2022
DOI: 10.1177/00952443221075505
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of natural rubber–based new elastomers for high-damping base isolation systems

Abstract: Natural rubber (NR)–based vulcanizates have been used as base isolation materials for many years. Combining good damping properties, low cost, and availability with acceptable mechanical and aging performance, these materials have always been the first choice for base isolation applications. In this research, we try to formulate a natural rubber base recipe with increased damping properties, which can fulfill mechanical and aging requirements of base isolation systems. For this purpose, a series of blends have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Natural rubber bearings (NRB), lead rubber bearings (LRB), high-damping rubber bearings (HDRB), slider bearings, and mono-, double-, and triple-friction pendulum (FP) systems stand out for their design simplicity and effectiveness. Some isolated structure projects and the development of new materials were described by De Luca and Guidi (2019) and Nobari Azar et al (2022). An isolation seismic layer must provide (i) low lateral stiffness, (ii) re-centering capacity, and (iii) supplementary damping.…”
Section: Introductionmentioning
confidence: 99%
“…Natural rubber bearings (NRB), lead rubber bearings (LRB), high-damping rubber bearings (HDRB), slider bearings, and mono-, double-, and triple-friction pendulum (FP) systems stand out for their design simplicity and effectiveness. Some isolated structure projects and the development of new materials were described by De Luca and Guidi (2019) and Nobari Azar et al (2022). An isolation seismic layer must provide (i) low lateral stiffness, (ii) re-centering capacity, and (iii) supplementary damping.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that both Friction Pendulum System (FPS) and Lead Rubber Bearing (LRB) isolation frames can effectively increase the seismic performance of structures (Zhao et al, 2022). Research shows that the pulse signal in pulsed ground motion will amplify the response of LRB base isolation structure (Nobari Azar et al, 2022). found that natural rubber base isolation can effectively meet the requirements of base isolation system (Rabiee and Chae, 2022).…”
Section: Introductionmentioning
confidence: 99%